AN OBSERVATION OF CLASSROOM ASSESSMENT PRACTICES AMONG LECTURERS IN SELECTED MALAYSIAN HIGHER LEARNING INSTITUTIONS (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ The study was aimed at exploring and analysing the current assessment practices of lecturers in selected Malaysian higher learning institution classrooms. The focus was the different modes of assessment used in the classroom and to make recommendations on using a variety of assessment modes that would be well-aligned with the intended learning outcomes.Methodology â€“ A qualitative approach using the descriptive case study design was employed in developing the study. Subjects of the study were selected based on a voluntary basis and 15 lecturers teaching in eight programmes from two higher learning institutions participated in the study. Classroom observation was the main method of data collection, while data analysis employed thematic analysis. Each lecturer was observed twice. Three instruments were used in data collection, namely: pre-observation form, observation form and video recordings. The data was analysed through the opencoding process. The notes in the observation forms were compiled and reviewed to identify themes. Findings â€“ The findings revealed that the current assessment practices of the lecturers included several modes of assessment, with oral questioning and peer assessment modes being used more frequently than others. The feedback modes employed were also varied with giving comments and correcting student answers or errors as the most common modes. The results provided evidence that besides teacher assessment, peer assessment was found to be another form of assessment favoured by the lecturers during the teaching and learning process. It was used to assess student presentations, to correct peer errors, and to give feedback.Significance â€“ The findings were used to guide decisions on the need for assessment training for lecturers, educators and curriculum developers regarding the types of assessment modes for incorporation in teaching and learning, and also the need for assessment training that would provide lecturers with the knowledge and confidence to use a variety of assessment modes.